Production cross sections of thulium radioisotopes for alpha-particle induced reactions on holmium - Usman, A. R.; Khandaker, Mayeen Uddin *; Haba, H.; Otuka, N.; Murakami, M. (Elsevier, 2020)
The production cross sections of 165–168Tm radioisotopes produced in α-particle induced reactions on 165Ho were measured from 49.6 MeV down to the respective thresholds using the stacked-foil activation technique and HPGe gamma-ray spectrometry. The measured excitation functions were compared with previous measurements as well as the TENDL-2019 library. We also calculated the thick target yields for all the assessed radioisotopes by integration of the measured excitation functions and found that they show good agreement with the directly measured thick target yields except for 168Tm production.